Regular Physical activity Based on transtheoretical Model among Health and Paramedic Schools of Golestan University of Medical Sciences - Abdurrahman Charkazi; Ladan Fazli; Fatemeh Alizadeh; Atefeh Fazelnia; Ghorban mohammad Koochaki; Fozieh Bakhsha (Iranian Association of Health Education and Health Promotion, 2014)
Background: Sedentary life is one of the most important risk factors for many diseases and disorders. Trantheoretical Model is one of the behavior study models, considering peoples readiness to behavioral change. The aim of the current study was to investigate regular physical activity based on transtheoretical model among Health and Paramedic Schools of Golestan University of Medical Sciences. Methods: in a cross-sectional analytic design in spring 2013, 403 undergraduate students who recruited through census method. Data gathered using by Marcus et al's, stages of change measure along with Nigg et al's, Decisional Balance, Self- Efficacy, and Processes of Change measures.Gathered data were analyzied through descriptive statistics, Chi-square, Kruskal-Wallis, Mann-whietny, and logistic regression tests in SPSS software ver.15. Result:Fourty four point three percent were in precontemplation stage, 5.2% in contemplation,40% in preparation, 3.5% in action, and 7% in maintanenec stage.There was a significant relationship between physical activity stage of change with cons , pros,self-efficacy,expirential and behavioral processes (p<0.05.( Sex varriable (OR=8.234, 95% CI:3.721-18.223( and behavioral processes of change (OR=2.259, 95% CI:1.388-3.676)were the most siginficant predictors of regular physical activity. Conclussion: The findings revealed that majority of the students especially ,female studentswere in the earlier stages of chang and have sedentary life.Stage-based appropriate interventions is necessity.